PERIOPERATIVE PROPHYLAXIS OF VENOUS THROMBOEMBOLISM IN ROUTINE ONCOSURGERY - V. E. Khoronenko; V. I. Chissov; P. A. Suvorin; D. S. Baskakov (Исследования и практика в медицине, 2016)
The article is devoted the problem of prevention of perioperative venous thromboembolic complications (VTEC) in cancer patients. The study identifies the causes of thrombosis in this category of patients and describes in details the major and minor risk factors for the development of VTEC. The results of studies on the influence of the morphological characteristics of the tumor, the stage and location of tumor on the risk of development of  VTEC are performed. It is noted that along with the likelihood of thrombosis, cancer patients at the stages of surgical treatment there is an alternative risk factor – bleeding. The frequency of hemorrhagic complications and their risk increases in the presence of disintegration of the tumor, its proximity to the main vessels, extent of surgical aggression, as well as due to the introduction of anticoagulants. The approaches to the selection of the optimal method is specific or nonspecific prevention of VTEC depending on the nature and volume of the intervention, estimated blood loss and patients’ rehabilitation time are described. We show the advantages of  low  molecular weight heparins compared with unfractionated heparin for the prevention of VTEC in Oncology. The article presents long-term experience of employees of one of the leading cancer institutions in Russia – P. Hertsen MORI, whose team took an active part in the development of Russian clinical guidelines for the prevention and treatment of VTEC in Oncology.